Crosslinked conjugated polymers as hole transport layers in high-performance quantum dot light-emitting diodes. Issue 3 (22nd March 2017) - Zou, Yatao; Liu, Ying; Ban, Muyang; Huang, Qi; Sun, Teng; Zhang, Qing; Song, Tao; Sun, Baoquan
Abstract : Photochemical crosslinked HTLs are developed for highly efficient all-solution-processed quantum dot light-emitting diodes. Abstract : Film morphologies of functional layers in all-solution-processed quantum dot light-emitting diodes (QLEDs) play a crucial role in device performance. Solvents for adjacent layers should be strictly orthogonal to prevent the preceding layer being redissolved by the processing solvent of the next layer. Herein, we use a photochemical crosslinking method to obtain solvent-resistant hole transport layers (HTLs) with photoinitiator bifunctional bis-benzophenone (BP-BP). With this method, ultra-smooth quantum dot (QD) layers can be fabricated using toluene as solvent, which is known to be a nonorthogonal solvent in common non-crosslinked HTLs. A green QLED device based on crosslinked HTLs exhibits a high external quantum efficiency of 8.93%, which is 1.9-fold higher than that of the non-crosslinked device. The improved device performance is ascribed to the well preserved film morphology of crosslinked HTLs and the prevention of QDs intermixing with HTLs during the QD deposition in toluene. This crosslinking strategy avoids high-temperature annealing, allowing the fabrication of flexible devices on plastic substrates. Moreover, it broadens the range of applicable solvents for solution-processed multilayer optoelectronic devices because non-orthogonal solvents can be used after crosslinking preceding layers.